2022
DOI: 10.3847/2041-8213/ac794d
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Weakened Magnetic Braking in Old Solar Analogs

Abstract: The rotation rates of main-sequence stars slow over time as they gradually lose angular momentum to their magnetized stellar winds. The rate of angular momentum loss depends on the strength and morphology of the magnetic field, the mass-loss rate, and the stellar rotation period, mass, and radius. Previous observations suggested a shift in magnetic morphology between two F-type stars with similar rotation rates but very different ages (88 Leo and ρ CrB). In this Letter, we identify a comparable transition in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…Stars akin to β Hydri are characterized by reduced outer atmospheric heating as well as a noticeably decreased level of chromospheric emission, with the latter confirmed by observations (e.g., Dravins et al 1993b;Buccino & Mauas 2008). Clearly, when stars evolve away from the main-sequence approaching the subgiant stage, the magnitude of magnetic activity is considerably reduced as a consequence of the restructuring of the stellar interior, associated with the redistribution of the angular momentum, and the loss of angular momentum due to the stellar wind (e.g., Schrijver & Pols 1993;Charbonneau et al 1997;Johnstone et al 2015); see also Metcalfe et al (2022) for updated analyses. Preliminary results for β Hyi based on theoretical twocomponent chromosphere models (acoustic and magnetic) have been given by Cuntz & Fawzy (2022), which also include some comparisons with observations.…”
mentioning
confidence: 82%
“…Stars akin to β Hydri are characterized by reduced outer atmospheric heating as well as a noticeably decreased level of chromospheric emission, with the latter confirmed by observations (e.g., Dravins et al 1993b;Buccino & Mauas 2008). Clearly, when stars evolve away from the main-sequence approaching the subgiant stage, the magnitude of magnetic activity is considerably reduced as a consequence of the restructuring of the stellar interior, associated with the redistribution of the angular momentum, and the loss of angular momentum due to the stellar wind (e.g., Schrijver & Pols 1993;Charbonneau et al 1997;Johnstone et al 2015); see also Metcalfe et al (2022) for updated analyses. Preliminary results for β Hyi based on theoretical twocomponent chromosphere models (acoustic and magnetic) have been given by Cuntz & Fawzy (2022), which also include some comparisons with observations.…”
mentioning
confidence: 82%
“…Preliminary support for this interpretation was identified (Metcalfe et al 2016) in measurements of the large-scale magnetic field strength and morphology from Zeeman Doppler imaging (Petit et al 2008) and was reinforced by the associated changes in stellar activity cycles (Metcalfe & van Saders 2017). Targeted observations for an evolutionary sequence of two stars slightly hotter than the Sun (Metcalfe et al 2019(Metcalfe et al , 2021, followed by a sequence of several solar analogs (Metcalfe et al 2022), provided the first direct evidence of a magnetic morphology shift in older solar-type stars and placed new constraints on the relative importance of various contributions to the overall reduction in the wind braking torque. Such constraints may ultimately help to identify a corresponding transition in the stellar dynamo.…”
Section: Introductionmentioning
confidence: 89%
“…This would challenge the current hypothesis of weakened magnetic braking (van Saders et al 2016), with angular momentum being more efficiently lost due to the favourable configuration of the stellar magnetic field and differential rotation pattern. It seems more likely that something prevents Sun-like stars from entering this configuration, or that a decreasing mass-loss rate could counteract this effect, producing the expected weakening of the wind-braking torque (discussed in Metcalfe et al 2022).…”
Section: Potential Impacts For Other Sun-like Starsmentioning
confidence: 99%
“…It has also been suggested that the wind-braking of Sunlike stars begins to decrease significantly around the age of the Sun (van Saders et al 2016;Metcalfe et al 2016;Booth et al 2017). Evidence for this has begun to grow thanks to new asteroseismic observations (Hall et al 2021), and models of the wind-braking torque for stars crossing the so called transition (Metcalfe & Egeland 2019;Metcalfe et al 2022).…”
Section: Introductionmentioning
confidence: 99%